Pengembangan Media Pembelajaran Pazel Kata Untuk Belajar Membaca Permulaan Siswa Kelas II SD Negeri 054914 Kota Lama - Monajar, Monajar; Basri, Amin (EDUTECH, 2025)
This study aims to develop a learning media in the form of word puzzles used to support the process of learning to read beginning in grade II Elementary School students. This study uses the Research and Development (RD) method with the ADDIE development model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study were grade II teachers and students of SD Negeri 054914 Kota Lama. The instruments used included expert validation questionnaires and practicality questionnaires for teachers and students. The validation results showed that the word puzzle media obtained a feasibility percentage of 75% from material experts, 90% from design experts, and 87% from language experts included in the "very feasible" category. Meanwhile, the results of the practicality test showed that teachers gave an assessment of 100% and students 89%, both of which were included in the "practical to use" category. Based on these results, it can be concluded that the word puzzle media is feasible and practical to use as an aid in learning to read beginning.